Demand-led extension: a gender analysis of attendance and key crops - Williams, Frances E.; Taron, Avinandan (Informa UK Limited, 2020)
Purpose: The need to increase women’s access to extension has been extensively discussed. This paper assesses women’s access to extension services through the Plantwise extension approach as a baseline for future comparison of women’s access through other extension approaches. It also assesses whether crops that men and women farmers seek plant health advice on are similar or not, and attempts to disperse assumptions that continue to be made about what crops women and men grow. Approach: We analysed data from the Plantwise Online Management System for 13 countries using descriptive and inferential statistics. Findings: We show that the Plantwise extension approach enables higher levels of women’s access than generally reported for agricultural extension, that the crops that women and men seek extension advice on is not gender dependent, and there are few clear distinctions between their crops of interest. Practical implications: There is limited literature studying gender inclusiveness in different extension approaches. The findings add to the documentation of assessing women’s access to demand-driven extension. Theoretical implications: Plantwise is a new extension approach which needs to be assessed from spatial and temporal perspectives to understand whether demand-driven extension enables increased women’s access over time. Originality/value: Extension service provision is often based on assumptions about what crops are being grown. Small studies have challenged these assumptions, but this large dataset enables us to test these assumptions more thoroughly across 13 countries adding to the weight of evidence against the existence of women’s and men’s crops.